1966
DOI: 10.1145/365170.365202
|View full text |Cite
|
Sign up to set email alerts
|

Euler

Abstract: In this section the algorithmic language EULER is described first informally and then formally by its syntax and semantics. An attempt has been made to generalize and extend some of the concepts of ALGOL, thus creating a language which is simpler and yet more flexible than ALGOL 60. A second objective in developing this language was to show that a useful programming language which can be processed with reasonable efficiency can be defined in rigorous formality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 0 publications
1
50
0
Order By: Relevance
“…Thus simple and weak precedence [12,15,8], for instance, use the (top-of-stack, lookahead) symbol pair to build precedence relations, and then to use them to know whether to shift or reduce. These methods fail when the needed information is deeper in the stack.…”
Section: Our Approach For Lr(1) Parsingmentioning
confidence: 99%
“…Thus simple and weak precedence [12,15,8], for instance, use the (top-of-stack, lookahead) symbol pair to build precedence relations, and then to use them to know whether to shift or reduce. These methods fail when the needed information is deeper in the stack.…”
Section: Our Approach For Lr(1) Parsingmentioning
confidence: 99%
“…We have a phrase "T + P" which we wou1d like to associate with the "a + b 11 but in the evaluation of the expression we do not add b to a. Actually, Grammar B "suggests" that "a+ b * C 11 be evaluated as:…”
Section: T2mentioning
confidence: 99%
“…The relationship between the class of reducing transition languages, introduced by Eickel, Paul, Bauer and Samelson [1], and the class of simple precedence languages, introduced by Wirth and Weber [2], was studied by Morris [3]. He showed that the latter class is a proper subset of the former and hinted that this first class was a proper subset of the deterministic context free languages.…”
Section: Introductionmentioning
confidence: 99%